Patients' Expectations Before and Evaluation After Dental Implant Therapy - Baracat, Lilian Fernandes; Teixeira, Amanda Marques; Fernandes dos Santos, Mateus Bertolini; Prisco da Cunha, Vicente de Paula; Marchini, Leonardo [UNESP] (Wiley-Blackwell, 2011)
Background:Patients' expectations may influence their satisfaction with implant treatment, but there is a paucity of reports comparing patient expectations and their posttreatment satisfaction.Purpose:The aim was to compare patients' expectations before with their satisfaction regarding function and esthetics after dental implant therapy.Materials and Methods:Fifty volunteers (49 years +/- 11.45) answered a questionnaire about influencing variables and underwent an initial examination followed by implant therapy. Their expectations regarding esthetics and function were verified on a visual analogue scale (VAS) before treatment. The VAS was also used for posttreatment completion rating.Results:The average ratings for esthetic and functional expectations were 5.0 +/- 2.6 and 5.0 +/- 3.0; the posttreatment completion ratings were 9.1 +/- 1.1 and 9.0 +/- 1.7, respectively. The posttreatment completion ratings significantly exceeded expectations (p < .001, Wilcoxon test). Positive correlations were found between expectations and posttreatment completion ratings for esthetics (Spearman's rho = 0.496, p < .001) and function (Spearman's rho = 0.706, p < .001). An inverse correlation was found between age and functional expectations (Spearman's rho = -0.313, p = .027).Conclusions:Patients' posttreatment completion ratings significantly exceeded their initial expectations. Expectations and posttreatment completion ratings were irrespective of smoking habits, location in the jaw, sex, or educational level.
Keywords: dental implants; patient expectations; patient satisfaction; success rates